2008
DOI: 10.1017/s0954422408125124
|View full text |Cite
|
Sign up to set email alerts
|

Grape products and cardiovascular disease risk factors

Abstract: Many in vivo trials have evaluated the effects of grape products on different CVD risk factors. Most published studies have dealt with some specific aspects of mechanisms of grape flavonoid action or have focused only on one product, such as wine. The aim of the present paper is to review trials dealing with grape products and CVD published during the last 13 years (seventyfive trials). Polyphenols, alcohol and dietary fibre are the main constituents of the tested products. In animal and human studies, grape p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 108 publications
(299 reference statements)
2
54
1
Order By: Relevance
“…Accumulating evidence indicates that grape polyphenols work in many different ways to decrease blood glucose [45], improve insulin resistance [46]- [48], suppress hyperinsulinemia [49], and reduce blood pressure and lipid concentration [50]- [53]. Consistently, our results showed that the plasma glucose and insulin mRNA expression was significantly decreased in the non-STZ treated mice fed with GPE.…”
Section: Discussionsupporting
confidence: 85%
“…Accumulating evidence indicates that grape polyphenols work in many different ways to decrease blood glucose [45], improve insulin resistance [46]- [48], suppress hyperinsulinemia [49], and reduce blood pressure and lipid concentration [50]- [53]. Consistently, our results showed that the plasma glucose and insulin mRNA expression was significantly decreased in the non-STZ treated mice fed with GPE.…”
Section: Discussionsupporting
confidence: 85%
“…Several grape products have been shown to reduce markers of inflammation or oxidative stress associated with cardiovascular disease in vivo, ex vivo and in vitro. 29,30 For example, consumption of red grape juice by hemodialysis patients, who suffer from hemodialysis-induced oxidative stress, reduced plasma levels of oxidized low-density lipoprotein and ex vivo neutrophil NAPDH oxidase activity. 31 Similarly, consumption of red grape juice decreased markers of oxidative stress in healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…These products have been used to treat a variety of conditions, including cancer, cardiovascular disease, ischemic stroke, neurodegenerative disorders, aging, hypertension, hyperlipedemia, and dental caries (Perez-Jimenez and Saura-Calixto 2008, Iriti and Faoro 2009, Kaur et al 2009, Nassiri-Asl and Hosseinzadeh 2009, Wu 2009, Yadav et al 2009). Although the chemical constituents of grapes and wine vary to some degree, similar therapeutic effects have been attributed to wine.…”
mentioning
confidence: 99%